2020
DOI: 10.1097/tp.0000000000003208
|View full text |Cite
|
Sign up to set email alerts
|

Nlrp3 Inflammasome Inhibitor MCC950 Ameliorates Obliterative Bronchiolitis by Inhibiting Th1/Th17 Response and Promoting Treg Response After Orthotopic Tracheal Transplantation in Mice

Abstract: Background. Obliterative bronchiolitis (OB) remains the major complication limiting long-term survival of patients after lung transplantation. We aimed to explore the effects of the selective NACHT, LRR, and PYD domains-containing protein 3 (Nlrp3) inflammasome inhibitor MCC950 on the pathogenesis of OB. Methods. Mouse orthotopic tracheal transplants were performed to mimic OB. MCC950 (50 mg/kg) or saline was intraperitoneally injected daily. The lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Chen et al have demonstrated that rapamycin-induced mitophagy further enhances the neuroprotection of inhibition of NLRP3 inflammasome activation by MCC950 following TBI (Chen et al, 2019d); this may be crosstalk with mtDNA and/or mtROS. MCC950 as an NLRP3 specificity inhibitor (Coll et al, 2019;Tapia-Abellán et al, 2019), the keywords in this bibliometric study, inhibits NLRP3 inflammasome activation and pyroptosis in a variety of disease models and improves disease process (Coll et al, 2015;Dempsey et al, 2017;Ren et al, 2020;Xu et al, 2020), but that does not alter wound healing in obese mice (Lee et al, 2018). A clinical trial involving 19 autoinflammatory syndrome patients reveals some key findings (Schuh et al, 2019): 1) peripheral blood mononuclear cells from patients with NLRP3 low penetrance variants are more likely to release NLRP3-specific IL-1β, which is demonstrated by inhibition of NLRP3 with MCC950; 2) these patients present NLRP3-independent release of IL-6 and TNF-α; and 3) patients with NLRP3 low penetrance variants may present with severe CNS manifestations and partially respond to IL-1 targeting therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al have demonstrated that rapamycin-induced mitophagy further enhances the neuroprotection of inhibition of NLRP3 inflammasome activation by MCC950 following TBI (Chen et al, 2019d); this may be crosstalk with mtDNA and/or mtROS. MCC950 as an NLRP3 specificity inhibitor (Coll et al, 2019;Tapia-Abellán et al, 2019), the keywords in this bibliometric study, inhibits NLRP3 inflammasome activation and pyroptosis in a variety of disease models and improves disease process (Coll et al, 2015;Dempsey et al, 2017;Ren et al, 2020;Xu et al, 2020), but that does not alter wound healing in obese mice (Lee et al, 2018). A clinical trial involving 19 autoinflammatory syndrome patients reveals some key findings (Schuh et al, 2019): 1) peripheral blood mononuclear cells from patients with NLRP3 low penetrance variants are more likely to release NLRP3-specific IL-1β, which is demonstrated by inhibition of NLRP3 with MCC950; 2) these patients present NLRP3-independent release of IL-6 and TNF-α; and 3) patients with NLRP3 low penetrance variants may present with severe CNS manifestations and partially respond to IL-1 targeting therapies.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq showed that the NF-кB signalling pathway was enriched in the patient’s M1 macrophages, and since apremilast acts via a NF-кB-dependent mechanism to reduce levels of inflammatory cytokines such as TNF [ 39 ], this may provide an explanation for the efficacy of this treatment. The IL-17 signalling pathway was also enriched in M1 macrophages, which is notable because NLRP3 inflammasome activation and IL-1β release have been linked to enhanced inflammatory Th17 cell responses in diseases including ankylosing spondylitis [ 40 ], inflammatory skin diseases including hidradenitis suppurativa [ 41 , 42 ], rheumatoid arthritis [ 43 ] and obliterative bronchiolitis [ 44 ]. A MWS-related NLRP3 mutation also caused spontaneous skin inflammation in mice due to increased IL-1β production and consequent Th17 cell predominance [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that activation of the NLRP3 inflammasome, an important component of innate immunity, is significantly elevated in mice receiving allogeneic tracheal grafts (168). Acquired immunity is also involved in the pathogenesis of BO.…”
Section: Bomentioning
confidence: 99%
“…In 2020, D'Amico et al (171) found that the formyl peptide receptor 1 gene deletion has a protective effect on BO induced by heterotopic tracheal transplantation in mice by regulating the signal transduction of NLRP3 inflammasome and reducing its activation. In 2020, Xu et al (168) found that in the orthotopic tracheal transplantation mouse BO model, NLRP3 inflammasome inhibitor MCC950 blocked the activation of NLRP3 inflammasome to reduce the production of pyroptosis-related cytokines IL-1b and IL-18, thus regulating the balance of Th1/ Th17 and Treg cells and improving BO lesions. Therefore, inhibiting the activation of NLRP3 inflammasome and inhibiting pyroptosis may be a new target for the treatment of BO.…”
Section: Bomentioning
confidence: 99%